Pengaruh Pengawasan Terhadap Produktivitas Karyawan Bagian Produksi PT. Riau Graindo Pekanbaru - Iskandar, Iskandar (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The purpose of this study was to determine the effect of supervision on the productivity of employees of the Production Division of PT. Riau Graindo Pekanbaru. To achieve this goal, a study was conducted using a sample of 31 people, using the census random method. The data analysis method used simple linear regression. Based on the results of the supervision test, it has a significant effect on the productivity of employees in the production division of PT. Riau Graindo Pekanbaru, this is proven based on the t-test found that t-count is greater than t-table (3.983 > 2.045). The value of R. Square (R2) of 0.354 (35.4%) explains that the supervision variable contributes to the productivity of employees in the production division of PT. Riau Graindo Pekanbaru by 35.4%. While the remaining 64.6% describes other independent variables that were not observed in this study. Recommendations that can be submitted It is hoped that the company can pay attention to employees so that employees in carrying out their work always think that today must be better than yesterday because this statement received the lowest response from respondents